Designing, implementation, and evaluation of internship comprehensive system for assessment and monitoring - Firouzeh Moeinzadeh; Sayed Hamid Reza Ayati; Bijan Iraj; Mojgan Mortazavi; Vajiheh Vafamehr (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: During the past decade, the benefits of using portfolios, especially electronic portfolios, were recognized. Due to the lack of using portfolios and especially electronic portfolio in the clinical evaluations of internship training in medical schools of Iran, this study has designed, implemented, and evaluated a comprehensive system for monitoring and evaluating the activities of interns. MATERIALS AND METHODS: This study was a software development study in the three phases of design, implementation, and evaluation. All stages of the project were carried out in the Isfahan University of Medical Sciences during 2019-2020. The software design phase was performed using the Rapid Application Development Methodology (RAD model). In the implementation phase, it was used as a pilot study in the internal department of the medical school. System evaluation was performed using a combination of quantitative and qualitative methods. Data were analyzed using the content analysis for qualitative data and descriptive statistical analysis using the SPSS software for quantitative data. RESULTS: In the educational standards survey, in 10 items, the percentage of choosing "perfectly fit" and "fit" was above 90% (high quality). In the technical standards questionnaire, out of 35 items related to software technical quality, eight items were of acceptable quality and 27 of them were partially acceptable. In the Student Satisfaction Questionnaire, in 9 items, interns' satisfaction with the system was high or very high, and in either case, there was little or no dissatisfaction or satisfaction. CONCLUSIONS: Positive educational effects can be used in all clinical settings if modification and improvement of the software continues, with slight modifications.